2016
DOI: 10.1016/j.jacc.2016.03.524
|View full text |Cite
|
Sign up to set email alerts
|

Ticagrelor for Prevention of Ischemic Events After Myocardial Infarction in Patients With Peripheral Artery Disease

Abstract: Among stable patients with prior MI, those with concomitant PAD have heightened ischemic risk. In these patients, ticagrelor reduced MACE, with a large absolute risk reduction, and MALE. (Prevention of Cardiovascular Events in Patients With Prior Heart Attack Using Ticagrelor Compared to Placebo on a Background of Aspirin [PEGASUS-TIMI 54]; NCT01225562).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
226
0
31

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 333 publications
(260 citation statements)
references
References 19 publications
3
226
0
31
Order By: Relevance
“…20 Patients with peripheral artery disease are also at increased risk of bleeding, which is partly explained by their high number of comorbid conditions such as advanced age and renal insufficiency. 7,8,23 In COMPASS, although an increase in major bleeding was observed in both rivaroxaban groups when compared with aspirin alone, there was no excess in fatal or critical organ bleeds, bleeding into a surgical site requiring reoperation, and no excess of major bleeding observed in the peripheral artery disease subgroup compared with the coronary artery disease subgroup. 29 Furthermore, most of the bleedings were gastrointestinal, which rarely leave permanent sequelae.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…20 Patients with peripheral artery disease are also at increased risk of bleeding, which is partly explained by their high number of comorbid conditions such as advanced age and renal insufficiency. 7,8,23 In COMPASS, although an increase in major bleeding was observed in both rivaroxaban groups when compared with aspirin alone, there was no excess in fatal or critical organ bleeds, bleeding into a surgical site requiring reoperation, and no excess of major bleeding observed in the peripheral artery disease subgroup compared with the coronary artery disease subgroup. 29 Furthermore, most of the bleedings were gastrointestinal, which rarely leave permanent sequelae.…”
Section: Discussionmentioning
confidence: 94%
“…7 Furthermore, single and dual antiplatelet regimens have not conclusively shown reductions in major adverse limb events. 10,20,22,23 Before COMPASS, the most promising therapies for patients with chronic stable peripheral artery disease were clopidogrel which was superior to aspirin to prevent major adverse cardiac events, 24 although the efficacy in preventing limb events was less clear; and the platelet receptor antagonist vorapaxar 12 used together with other antiplatelet drugs. In TRA2P-TIMI 50, 12 although the composite of cardiovascular death, myocardial infarction, and stroke was reduced with vorapaxar in the overall trial, no significant benefit was observed in patients with peripheral artery disease, and there was more moderate or severe bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…114 Similarly, recent clinical trials that included patients with symptomatic PAD demonstrated that 1 in 5 patients with PAD undergo revascularization at 3 years. 115, 116 As discussed before, patients with obstructive PAD, regardless of limb symptom characteristics, have functional impairment. As shown in the Table, available medical treatment modalities to improve limb function and outcome include exercise therapy and antiplatelet therapy.…”
Section: Treatment Of Limb Symptoms In Padmentioning
confidence: 96%
“…3,8,14,15,17 ALI required both a clinical presentation consistent with acute ischemia (symptoms consistent with a rapid or sudden decrease in limb perfusion lasting <2 weeks) including findings on physical examination or imaging. 17 In addition, all peripheral artery revascularization and amputation procedures were recorded by the site in the electronic case report form.…”
Section: What Are the Clinical Implications?mentioning
confidence: 99%
“…[1][2][3] Thus, patients with symptomatic PAD are at heightened risk of major adverse cardiovascular events (MACE) including myocardial infarction, stroke, and cardiovascular death. 4,5 In addition, it is important to note that patients with PAD experience significant morbidity from major adverse limb events (MALE) including acute limb ischemia, urgent peripheral revascularization, and major amputation.…”
mentioning
confidence: 99%